Characteristics of salvadoran spanish (Educational Knowledge, 2023)
Salvadoran Spanish has evolved over a long history, developing from interactions between Spanish colonizers and indigenous populations. This dialectal variant, distinct from others and even featuring voseo (use of “vos” instead of “tú”), emerged through collaboration between the two groups. The article challenges the notion of Spanish imposition or Nahuatl (indigenous language) Spanishization, instead emphasizing the Nahuatlization of Spanish due to the Spanish speakers’ lack of necessity to learn Nahuatl, which was dominant in the region. This linguistic interplay contributed to the Salvadoran Spanish lexicon and dialect configuration. The study aligns with Geoffroy Rivas’ postulates, evident in verb usage and word formation and transformation.
Keywords: Language; dialect; speech; metaplasm; Nahuatl; nahuatlization; polysynthesis